An update on brown adipose tissue and obesity intervention: Function, regulation and therapeutic implications - Liu, Xiaomeng; Zhang, Zhi; Song, Yajie; Xie, Hengchang; Dong, Meng (Frontiers in Endocrinology, 2023)
Overweight and obesity have become a world-wide problem. However, effective intervention approaches are limited. Brown adipose tissue, which helps maintain body temperature and contributes to thermogenesis, is dependent on uncoupling protein1. Over the last decade, an in-creasing number of studies have found that activating brown adipose tissue and browning of white adipose tissue can protect against obesity and obesity-related metabolic disease. Brown adipose tissue has gradually become an appealing therapeutic target for the prevention and re-versal of obesity. However, some important issues remain unresolved. It is not certain whether increasing brown adipose tissue activity is the cause or effect of body weight loss or what the risks might be for sympathetic nervous system-dependent non-shivering thermogenesis. In this review, we comprehensively summarize approaches to activating brown adipose tissue and/or browning white adipose tissue, such as cold exposure, exercise, and small-molecule treatment. We highlight the functional mechanisms of small-molecule treatment and brown adipose tissue transplantation using batokine, sympathetic nervous system and/or gut microbiome. Finally, we discuss the causality between body weight loss induced by bariatric surgery, exercise, and brown adipose tissue activity.